국내 육성 옥수수 품종의 곡실 성분 특성 - 정건호(Gun-Ho Jung); 김미정(Mi-Jung Kim); 손범영(Beom-Young Son); 김선림(Sun-Lim Kim); 윤미라(Mi-Ra Yoon); 곽지은(Jieun Kwak); 최인덕(Induck Choi); 곽강수(Kang-Su Kwak); 이춘기(Choon-Ki Lee) (Korean journal of breeding, 2016)
This study was carried out to evaluate the proximate contents and compositions of amino acids and fatty acids in Korean 6 dent, 2 intermediate, and 3 semiflint maize (Zea mays L.) hybrids. The protein content of 11 Korean maize hybrids ranged from 9.0% (Pyeonggangok) to 11.5% (Jangdaok). The crude fat content varied from 4.0% (Pyeonggangok and Yanganok) to 5.6% (Kwangpyeongok), and the crude ash content was 1.3 (Jangdaok) ~ 1.6% (Cheonganok). Total starch contents of maize hybrids were determined in the range of 51.4% (Jangdaok) to 70.9% (Cheonganok). Major amino acid in maize varieties were glutamic acid (27.28~28.68%) and followed by proline, alanine, and aspartic acid. Fatty acid were mainly composed of oleic acid (C18:1, 23.55~31.47%) and linoleic acid (C18:2, 47.55~56.64%) in maize hybrids. Cheonganok, Cheongdaok, and Kwangpyeongok had high oleic acid composition among Korean maize hybrids. Also, Gangdaok and Kwangpyeongok had high composition of saturated fatty acid. Because kernel composition affects maize quality, it is important data for the maize breeding program and food processing.